CHINESE TOURISTS’ EXPENDITURES IN THE POST COVID-19 ERA WHAT BRINGS THEM TO A DESTINATION - Benitez Garcia, Antonio (Global journal of Business and Integral Security, 2022)
The purpose of this research is to identify the current interests and variables that the Chinese Market is considering for traveling, during and after the challenges of Covid-19. The study aims to analyze the results from the methods of Pearsons Correlation Coefficient, Cramers V based in Chi-square test, and individual answers from all the respondents, by categories from leisure to business travelers. The results show the level of importance that this niche conveys to the impact of some variables, ranking highest to Security in the destination, where there is no criminality. Second, the Health concerns coverage, where the destinations are able to secure the health and hygiene capacity to provide a safety holidays or business trip. Third, good relationship between China and the potential visited destination. There is also a correlation, no causation, with other variables such as Income, Education, Accessibility, among others, as these are considerations for traveling, in different percentages for business and leisure.